Post-Covid-19 tourist reactivation of protected natural areas and its impact on improving the experience of tourists in Ecuador - Herrera Anangonó, Roberto Carlos (2021)
In Ecuador there are 61 protected areas corresponding to 20.35 % of the national territory.  This research aims to define the tourist characterization, establish the profile of the visitor around the motivations and preferences of infrastructure and post-Covid 19 security to improve the experience of tourists in natural spaces. Visitors between the ages of 19 and 35 come to natural areas as a family, motivated by natural attractions (95 %). To improve the experience of tourists, some strategies are established based on their perception and motivations. The information is managed by social networks (85 %), to access food and accommodation services. They prefer activities such as nature tourism and ecotourism (78 %), with facilities such as trails, bicycle paths and hygienic services, as well as biosecurity measures with the availability of dispensers, disinfectants, and personal hygiene supplies (73 %) and the presence of personnel with first aid abilities. Adapting security and biosecurity strategies improves the expectation and experience of tourists in protected areas in Ecuador.